ENHANCING THE ROLE OF STRATEGIC MANAGEMENT IN ADVANCING THE SUSTAINABILITY OF ISLAMIC FINANCIAL INSTITUTIONS - Yulitasari, Lis; Salma, Aulia Mutiara; Suhendar, Suhendar (JURNAL MANAJEMEN DAKWAH, 2025)
The increasing complexity of global economic competition and the rapid transformation of the financial industry present significant challenges to the sustainability of Islamic financial institutions. These challenges are further amplified by the necessity to align financial performance with ethical, social, and environmental responsibilities as mandated by the principles of maqasid al-shariah. Despite the growing discourse on sustainable finance, limited studies have integrated the domains of strategic management, sustainability, and Shariah compliance into a unified conceptual framework tailored to the specific context of Islamic financial institutions. This study aims to analyze and synthesize the role of strategic management in advancing sustainability within Islamic financial institutions, offering a comprehensive perspective that bridges theoretical insights and practical applications. The research adopts a literature review method, systematically examining and synthesizing relevant academic works, policy documents, and best practices from global and regional contexts. The findings indicate that embedding sustainability principles into the core of strategic management not only enhances institutional competitiveness and resilience but also strengthens public trust, expands financial inclusion, and ensures long-term socio-economic contributions. Furthermore, the study reveals that an integrated approach combining visionary strategic planning, adherence to maqasid al-shariah, and proactive adaptation to technological and regulatory changes serves as a robust foundation for sustainable growth. It is concluded that sustainability should be institutionalized as a strategic imperative, supported by clear performance indicators, capacity-building programs, and technology-driven innovations. The study recommends that Islamic financial institutions engage in constructive collaboration with regulators, industry associations, and stakeholders to foster an enabling ecosystem for inclusive and sustainable development. This conceptual synthesis not only contributes to the academic discourse but also provides actionable insights for policymakers and practitioners seeking to reinforce the long-term viability of Islamic financial institutions in the evolving global financial landscape.